Activation of FCGR2A enhances the antitumor efficacy of hPSC-derived CAR-M - Yang, Xinzhi; Li, Lu; Zhu, Sijing; Li, Shengtao; Wang, Xinlu; Han, Yuling; Yang, Liuliu (Frontiers in Cell and Developmental Biology, 2026)
IntroductionChimeric antigen receptor macrophages (CAR‐Ms) represent a novel approach in cellular immunotherapy. Human pluripotent stem cells (hPSCs) provide an unlimited and renewable cell source, enabling scalable and standardized production of CAR‐Ms with consistent quality.MethodsIn this study, we established a robust differentiation protocol to generate CAR‐Ms from hPSCs. To evaluate HER2‐directed hPSC‐derived CAR-M functionality, we first profiled HER2 expression across multiple tumor cell lines and identified SKOV3 as the optimal target due to its high HER2 level. CAR constructs incorporating intracellular domains from CD3ɛ, FCGR1A, FCGR2A, FCGR2B, and FCGR3A were introduced into hPSCs via lentiviral transduction.ResultsImportantly, CAR expression did not impair hPSCs differentiation into macrophages. Functional assays revealed that all CAR-Ms exerted cytotoxic effects on HER2‐positive SKOV3 cells, with FCGR2A‐based CAR-Ms demonstrating the strongest activity. Furthermore, polarization of CAR‐Ms into a proinflammatory state significantly enhanced tumor‐killing efficacy, particularly in FCGR2A CAR‐Ms.DiscussionThese findings highlight the potential of FCGR2A as an optimal signaling domain for CAR‐M design and underscore the therapeutic promise of proinflammatory polarized CAR‐Ms in solid tumor immunotherapy.